2021
DOI: 10.1002/ar.24686
|View full text |Cite
|
Sign up to set email alerts
|

Burrowing in blindsnakes: A preliminary analysis of burrowing forces and consequences for the evolution of morphology

Abstract: Burrowing is a common behavior in vertebrates. An underground life-style offers many advantages but also poses important challenges including the high energetic cost of burrowing. Scolecophidians are a group of morphologically derived subterranean snakes that show great diversity in form and function.Although it has been suggested that leptotyphlopids and anomalepidids mostly use existing underground passageways, typhlopids are thought to create their own burrows. However, the mechanisms used to create burrows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Similar levels of resolution were reported in other amphisbaenians (Amphisbaena gonavensis, A. kingii, A. vanzolinii, Allemand, 2017), scolecophidian snakes (Typhlophis squamosus, Rhinotyphlops schlegelii, Allemand et al, 2017;Typhlops jamaicensis, Scanferla, 2022), and alethinophidian snakes (Uropeltis woodmasoni, Olori, 2010; U. pulneyensis, Allemand et al, 2017;Teretrurus sanguineus, Scanferla, 2022). All these taxa being fully fossorial (e.g., Herrel et al, 2021;Kearney, 2003;Navas et al, 2004;Olori & Bell, 2012), this suggests that weak endocranial resolutions for the optic tectum, pituitary and ventral diencephalon are common in burrowing squamates that spend prolonged periods of time underground and are capable of penetrating substrates of higher resistance (Scanferla, 2016). In contrast, these brain regions are distinguishable from the endocast reconstructed here for the cryptozoic lizard Melanoseps, defined as such as it mostly uses the softer top compartment of the soil for burrowing (Malonza & Bwong, 2011;Scanferla, 2016), and similar levels of endocranial resolution were observed in two cryptozoic alethinophidian snakes, Anilius scytale and Atractaspis irregularis (Allemand et al, 2017;Scanferla, 2022).…”
Section: Neuroanatomical Resolutions Of Squamate Endocastsmentioning
confidence: 99%
“…Similar levels of resolution were reported in other amphisbaenians (Amphisbaena gonavensis, A. kingii, A. vanzolinii, Allemand, 2017), scolecophidian snakes (Typhlophis squamosus, Rhinotyphlops schlegelii, Allemand et al, 2017;Typhlops jamaicensis, Scanferla, 2022), and alethinophidian snakes (Uropeltis woodmasoni, Olori, 2010; U. pulneyensis, Allemand et al, 2017;Teretrurus sanguineus, Scanferla, 2022). All these taxa being fully fossorial (e.g., Herrel et al, 2021;Kearney, 2003;Navas et al, 2004;Olori & Bell, 2012), this suggests that weak endocranial resolutions for the optic tectum, pituitary and ventral diencephalon are common in burrowing squamates that spend prolonged periods of time underground and are capable of penetrating substrates of higher resistance (Scanferla, 2016). In contrast, these brain regions are distinguishable from the endocast reconstructed here for the cryptozoic lizard Melanoseps, defined as such as it mostly uses the softer top compartment of the soil for burrowing (Malonza & Bwong, 2011;Scanferla, 2016), and similar levels of endocranial resolution were observed in two cryptozoic alethinophidian snakes, Anilius scytale and Atractaspis irregularis (Allemand et al, 2017;Scanferla, 2022).…”
Section: Neuroanatomical Resolutions Of Squamate Endocastsmentioning
confidence: 99%
“…Overall, the shape of the premaxilla and its contacts with both the nasals and the maxilla, well‐developed nasofrontal articulation and nasal‐prefrontal contact suggests that Hypoptophis is able to burrow at least through loose substrate. In a recent study by Herrel et al ( 2021 ), it has been demonstrated that scolecophidians mainly use anteriorly directed force during burrowing. Observations of live specimens of Hypoptophis are needed to validate the hypothesis that it is an active burrower, and if so, to study the functional morphological aspects of digging.…”
Section: Discussionmentioning
confidence: 98%
“…Relative head width, however, has been shown to constrain burrowing efficiency in terrestrial burrowing vertebrates where diameter scales exponentially with the amount of work required to compress substrate during the burrowing process (Herrel et al, 2021; Navas et al, 2004). Skull diameter then likely functions as a hard constraint among burrowing wrasses and restricts the regions of morphospace that these species can explore and occupy.…”
Section: Discussionmentioning
confidence: 99%